2011
DOI: 10.1007/s12273-010-0012-5
|View full text |Cite
|
Sign up to set email alerts
|

Case study of window opening behavior using field measurement results

Abstract: Window opening behavior has significant influences on indoor environment and energy consumption in residential buildings. As a response to indoor environment, the control mechanism (window and interior door open/closed) should be studied first by comprehensive understanding of the variation of indoor environmental conditions. For this reason, a field measurement of environmental conditions was carried out in five representative apartments in Beijing from April to May in 2010. By comparison analyses of the fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…So, while the Balcony dimensions (2.5m by 1.4m) were based on those of a typical Toronto MURB, the Apartment was much smaller than an actual apartment. The wall area of the apartment adjacent to the balcony was 5.5m 2 compared with the wall area of an example two-bedroom apartment which was exposed to the exterior (33m 2 ). This resulted in Apartment heating loads which were significantly less than a typical two-bedroom apartment in Toronto.…”
Section: Laboratory Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…So, while the Balcony dimensions (2.5m by 1.4m) were based on those of a typical Toronto MURB, the Apartment was much smaller than an actual apartment. The wall area of the apartment adjacent to the balcony was 5.5m 2 compared with the wall area of an example two-bedroom apartment which was exposed to the exterior (33m 2 ). This resulted in Apartment heating loads which were significantly less than a typical two-bedroom apartment in Toronto.…”
Section: Laboratory Apparatusmentioning
confidence: 99%
“…Controlling interior conditions in these buildings can be challenging due to the adverse effects of leaky envelopes exacerbated by stack and wind pressure differences that lead to ineffective corridor pressurization. As a result, in an attempt to regulate their suite temperature in this centrally-controlled system, occupants will often open their windows during cold weather periods [2].…”
Section: Introductionmentioning
confidence: 99%
“…Kavgic et al [20] indicated that energy models often use standard air temperatures, such as the model default air temperatures used in the Traditional Approach, instead of air temperatures based on empirical data. However, interior air temperatures are not just the product of thermostat settings but they are also a 8 product of occupant behaviour as demonstrated by Jian et al [21] in their observation of the effect of window operation on suite temperature.…”
Section: Suite Conditions Comparisonmentioning
confidence: 99%
“…Window opening is an indication of occupants' dissatisfaction with their interior environment [21]. Through window displacement and temperature data, it was determined that residents of the subject building open their windows frequently, even during cold weather periods.…”
Section: Other Parametersmentioning
confidence: 99%
“…Building occupants' behaviour also significantly impacts the building energy performance. It is very difficult to deterministically represent their behaviour due to its temporal (usage of a specific appliance) or spatial (usage of a specific room) stochastic nature [8,9]. Wang et al [10] developed a model to simulate the occupant movement process based on the Markov chain.…”
Section: Introductionmentioning
confidence: 99%